Strategi 5W 1H Sebagai Alat Untuk Meningkatkan Pemahaman Teks Informasi Siswa Kelas 5 di SDN Wonokusumo V/44 Surabaya - Yayuk Setyowati (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
Basic education plays a crucial role in building the foundation of students' knowledge and skills, particularly in understanding informational texts. This ability is essential for comprehending everyday reading materials and preparing students for higher-level learning. However, understanding informational texts often poses a challenge for grade 5 students in Indonesia. This study aims to examine the effectiveness of the 5W 1H strategy in improving the understanding of informational texts for grade 5 students at SDN Wonokusumo V/44. This research employed a quasi-experimental design with a single group pre-test and post-test approach, involving 32 students selected through purposive sampling. The research instruments included text comprehension tests, observation sheets, and student questionnaires. The results revealed a significant improvement in understanding informational texts after implementing the 5W 1H strategy, with an average pre-test score of 57.17 and a post-test score of 81.17. Statistical analysis showed a t-value of -36.80 with a p-value of 6.80e-26, confirming a statistically significant difference. Observations and student questionnaires indicated an increase in student engagement and activity in the learning process. Students reported that the 5W 1H strategy helped them understand informational texts more easily and made the learning process more engaging. This strategy also assisted students in remembering important information from the texts they read. The study highlights the importance of the 5W 1H strategy as an effective learning tool for improving the comprehension of informational texts among elementary school students. By adopting this strategy, teachers can help students develop the critical and analytical thinking skills needed to understand various information in both everyday life and academic contexts. Furthermore, this research makes a practical contribution by developing a model for implementing the 5W 1H strategy that can be applied by other teachers in similar contexts. It also explores the potential for integrating technology in applying this strategy, which can further enrich students' learning experiences.